2003
DOI: 10.1128/iai.71.12.7140-7148.2003
|View full text |Cite
|
Sign up to set email alerts
|

Role for Complement in Development ofHelicobacter-Induced Gastritis in Interleukin-10-Deficient Mice

Abstract: The mechanisms by which the immune response can eradicate gastric Helicobacter infection are unknown. We hypothesized that Helicobacter-induced activation of the complement system could promote both inflammation and eradication of Helicobacter from the stomach. In vitro studies demonstrated that Helicobacter felis activates complement in normal mouse serum but not in serum from Rag2 ؊/؊ mice, indicating that H. felis activates complement through the classical pathway. Next, we infected complement-depleted wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 49 publications
1
27
0
1
Order By: Relevance
“…In addition, our study is the first to show that IL-10 Ϫ/Ϫ mice develop stronger protection than WT mice following oral immunization. Thus, elicitation of IgA and IL-10 locally in the gastric mucosa appears to be a successful strategy used by H. pylori bacteria to evade host protection against infection (20,21,30,31). In contrast, in the absence of IgA and IL-10, immunized mice developed the strongest protection as compared with that induced in WT mice.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, our study is the first to show that IL-10 Ϫ/Ϫ mice develop stronger protection than WT mice following oral immunization. Thus, elicitation of IgA and IL-10 locally in the gastric mucosa appears to be a successful strategy used by H. pylori bacteria to evade host protection against infection (20,21,30,31). In contrast, in the absence of IgA and IL-10, immunized mice developed the strongest protection as compared with that induced in WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, an inhibiting effect of IgA Abs on complement activation could account for the reduced inflammatory response seen in the IL-10 Ϫ/Ϫ mice. In fact, a recent report demonstrated that infection in IL-10 Ϫ/Ϫ mice with H. felis resulted in increased levels of serum complement and when complement was depleted in these mice they exhibited decreased gastritis, which delayed the clearance of bacteria (31). It has also been shown that human IgA Abs can significantly inhibit the activation of complement stimulated by Ag-bound IgG Abs (44).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations